THE IMPLEMENTATION OF STUDENT PORTFOLIOS TO IMPROVE GRADE 9 STUDENTS’ POSITIVE ATTITUDES TOWARD ASSESSMENTS AT AN INTERNATIONAL SCHOOL IN BOGOR - Kumalasari, Maria Yashinta Putri; Agustin, Atalya; Hidayat, Dylmoon (JOHME: Journal of Holistic Mathematics Education, 2020)
As an integral part of learning, assessments play important roles in determining the effectiveness of students’ learning. However, in a grade 9 extended mathematics class at an International located in Bogor, it was found that the students showed negative behaviors during the test and learning processes as a manifestation of their attitudes toward assessments. Therefore, the Classroom Action Research modelled by Robert Pelton was conducted to improve students’ positive attitudes toward both formative assessment and summative assessment. As a result, by implementing the student portfolios in sixteen meetings, the students’ positive attitudes toward assessments were developing. This improvement was influenced by the involvement of cognitive, affective, and behavioral responses while the students were developing the student portfolios in this CAR scope and sequence.